Fast camera observations of injected and intrinsic dust in TEXTOR. (13th November 2015) - Shalpegin, A; Vignitchouk, L; Erofeev, I; Brochard, F; Litnovsky, A; Bozhenkov, S; Bykov, I; den Harder, N; Sergienko, G
Abstract: Stereoscopic fast camera observations of pre-characterized carbon and tungsten dust injection in TEXTOR are reported, along with the modelling of tungsten particle trajectories with MIGRAINe. Particle tracking analysis of the video data showed significant differences in dust dynamics: while carbon flakes were prone to agglomeration and explosive destruction, spherical tungsten particles followed quasi-inertial trajectories. Although this inertial nature prevented any validation of the force models used in MIGRAINe, comparisons between the experimental and simulated lifetimes provide a direct evidence of dust temperature overestimation in dust dynamics codes. Furthermore, wide-view observations of the TEXTOR interior revealed the main production mechanism of intrinsic carbon dust, as well as the location of probable dust remobilization sites.